2021
DOI: 10.1186/s12889-020-10132-6
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility trial of parent HPV vaccine reminders and phone-based motivational interviewing

Abstract: Background We assessed the feasibility and acceptability of a sequential approach of parent-targeted HPV vaccine reminders and phone-based Motivation Interviewing (MI). Methods In 2016, we selected all 11- to 12-year-old boys and girls seen in one clinic whose vaccine records did not include the HPV vaccine (n=286). By gender, we individually randomized parents of adolescents to an interactive text message (74 girls and 45 boys), postcard reminder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…47 A study in the USA evaluated the use of reminders via postcards and text messages, including the conduct of motivational interviewing phone calls guided by a licensed clinical psychologist, which proved feasible and acceptable to parents who were targeted with HPV vaccine reminder messages. 48 The results echoed findings in another study in the USA that used 19 different text-based nudges (varied based on timing and contents of the messages) developed by behavioural scientists and designed to increase influenza vaccine uptake. 49 Overall, results showed a statistically significant boost in vaccination across the nudges, but the top-performing nudge was a reminder that said 'an influenza vaccine has been reserved for you', which was associated with an 11% increase in vaccination uptake.…”
Section: Make Available Information Salientmentioning
confidence: 54%
See 2 more Smart Citations
“…47 A study in the USA evaluated the use of reminders via postcards and text messages, including the conduct of motivational interviewing phone calls guided by a licensed clinical psychologist, which proved feasible and acceptable to parents who were targeted with HPV vaccine reminder messages. 48 The results echoed findings in another study in the USA that used 19 different text-based nudges (varied based on timing and contents of the messages) developed by behavioural scientists and designed to increase influenza vaccine uptake. 49 Overall, results showed a statistically significant boost in vaccination across the nudges, but the top-performing nudge was a reminder that said 'an influenza vaccine has been reserved for you', which was associated with an 11% increase in vaccination uptake.…”
Section: Make Available Information Salientmentioning
confidence: 54%
“…use of motivational interviewing phone calls to parents to address commonly asked questions about vaccine. 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, parental acceptability of the intervention was high, and this may inform any future adaptations of the intervention. The acceptability of reminders has previously been reported, such as text messages for early childhood vaccination and postcards and interactive text messages for human papillomavirus vaccines . A study that examined 3 delivery methods of vaccination reminders for adolescent vaccination found that although postal mail reminders were preferred by most participants, text messaging and email were more effective …”
Section: Discussionmentioning
confidence: 99%
“…Reno et al (2019) also found that motivational interviewing, coupled with a fact sheet, was helpful in motivating vaccination among hesitant parents [19] . However, motivational interviewing has been criticized for being time consuming and impractical [25] . Having resources available in advance for hesitant parents to review could help save time in the clinic.…”
Section: Discussionmentioning
confidence: 99%